Pengaruh Motivasi Kerja Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada PT. Federal International Finance (FIF) - Eka Pariyanti; Rinnanik Rinnanik; Tri Mardiono (STIE Mandala Jember, 2019)
Fulfill all needs or desires in the employee, it will create a feeling of satisfaction, and employees with high levels of satisfaction will experience an increase in performance. Based on this matter, this study aims, (1) To determine the effect of work motivation on employee performance, (2) To determine the effect of work motivation on job satisfaction, (3) To determine the effect of job satisfaction on employee performance, (4) To determine the effect work motivation on employee performance with job satisfaction as an intervening variable. The data collection technique of this study was a questionnaire and documentation. The population of this study was employees of PT. PT. Federal International Finance (FIF), eastern Lampung region with a total of 96 people. While the data analysis uses regression analysis and phat path. The results of this study are, (1) Motivating Work Influence on Employee Performance, (2) Motivating Influential Work Against Job Satisfaction, (3) Influential Job Satisfaction on Employee Performance, (4) Job Satisfaction Role as Intervening Variables Between Work Motivation and Performance Employees (5) Work motivation influences employee performance directly, but work motivation will have greater influence on employee performance if first through or added to job satisfaction. These Research Results Can Become Input For PT. Federal International Finance (FIF), as material for consideration to improve employee performance.